The Effect of Augmented Reality Acceptance on E-Commerce on Cosmetic Purchase Decisions Using Combination TPB and TAM - Khoirunnisa, Oktaria Gina; Sugiharti, Endang (Department of Computer Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, 2023)
The fact that the sales of cosmetic products in Indonesia are increasing causes competition between brands to be unavoidable. One of the strategies the company prepared is to expand its marketing reach with e-commerce. But when selling cosmetic products by online new problem arises, scilicet the absence of a tester causes a lack of information about the product and how the technology is accepted. A lack of understanding about the product will affect consumer buying interest. Shopee answers this problem by providing a markerless augmented reality-based beauty cam feature. Based on this description, this study will analyze the effect of acceptance of the use of augmented reality on product purchase decisions using a combination of the Technology Acceptance Model and Theory of Planned Behavior. Data in his study was collected by distributing online questionnaires to Shopee users who have used this feature. The results of this study indicate that behavioral control variables do not affect a person's behavioral intention to use the beauty cam feature or the intention to buy cosmetic products. In addition to these correlations, all proposed correlations have a significant effect. The results of this study can stimulate future research and become a consideration for feature developers and business owners in other fields.